Kajian Yuridis Putusan Mahkamah Agung Nomor 834 K/Pdt.Sus/2009 Mengenai Pembatalan Kepailitan Pt. Cipta Televisi Pendidikan Indonesia - Herman Susetyo, Hendro Saptono, Emmanuel Yoga Satria, (Diponegoro Law Journal, 2012)
The Commercial Court acced bankruptcy plea of Crown Capital against PT Cipta Televisi Pendidikan Indonesia because it has been considered to fulfil unassuming evidentiary requirements as stated on Article 8 paragraph (4) UU No. 37 of 2004 about Bankruptcy and PKPU. However, panel of judges of the commercial court’s argument being ruled out through Cassation Verdict No. 834 K/Pdt. Sus/2009 on 15th December 2009 by stated that the existence a quo debt apperently still in issue since it’s still being debated and disputed. Therefore, the requirements to be declared as bankrupt as stated on Article 8 paragraph (4) jo. Article 2 paragraph (1) ) UU No. 37 of 2004 about Bankruptcy and PKPU could not be fulfilled so bankruptcy plea has to be rejected. As the explanation above, the research purposed to understand  Panel of Judges State Court’s verdict who acced bankruptcy plea as stated on UU Bankruptcy and Suspension of  Payment. This research also to find out how Panel of Judges on Commercial Court and Supreme Court interprented of debt related with bankruptcy plea against TPI. Formulation of problems researched by using a research method: normative juridical approach. Descriptive analytical study to identified draft and law principles which being used to regulate bankruptcy in Indonesia, especially as basic framework on UU No. 37 of 2004 about Bankruptcy and Suspension of  Payment and UU No. 40 of 2007 about PT. Based on the result of the research, writer concluded that Panel of Judges on Commercial Court’s verdict which acced bankruptcy plea against TPI is incompatible with UU Bankruptcy and Suspension of  Payment wherefore did not fulfil unassuming simple evidentiary requirements since debt existence which being disputed on this case has to proved further on which its evidence tend to be not unassuming.